Peran Guru dalam Menentukan Model Pembelajaran Berbasis Proyek (PjBL) di Kelas Rendah Upaya untuk Meningkatkan Minat Belajar Peserta Didik di Sekolah - Damayanti, Nur Afni (Jurnal Pendidikan Guru Sekolah Dasar, 2024)
The role of teachers in the context of developing project-based learning models (PjBL) in lower grades has a significant impact on increasing students' interest in learning at school. This literature study analyzes teachers' contributions in designing and implementing PjBL as a strategy to enrich students' learning experiences. The teacher as the main facilitator in PjBL plays a role in determining the key aspects of the learning model. In the literature, it is found that teacher expertise in identifying projects that suit the curriculum and students' level of understanding is a crucial first step. The teacher's ability to integrate PjBL with lesson material opens up opportunities to increase understanding of concepts holistically. The importance of the teacher's role is also reflected in his ability to guide students during the project learning process. In the literature, emphasis on the teacher's role as a guide and motivator for students to actively participate, collaborate and solve problems is identified as the main element that influences the effectiveness of PjBL. This research examines various views and findings regarding the role of teachers in implementing PjBL in lower grades. The results provide insight into how teachers can be the main catalyst for increasing students' interest in learning through this innovative learning model. It is hoped that a deeper understanding of the role of teachers in PjBL can provide guidance for the development of more effective education and teacher training policies.